A New Technique to Puncture and Remove a PTCA Balloon that Fails to Deflate - Pasamanickam, Kannan; Rajadurai, Jeyamalar; Choo, Gim-Hooi (International Journal of Angiology, 2020)
We present the first clinical report and describe the technique of using a modified Heartrail II guiding catheter to successfully puncture and remove a coronary angioplasty balloon that failed to deflate after stent implantation.
Keywords: coronary; angioplasty balloon; puncture; balloon failure; deflate; stent; Heartrail catheter